Examine sex differences in autism spectrum disorder in school-aged children and adolescents with fluent language - Ji, Yan; Ji, Yue; Zhu, Hui-lin; Cheng, San-mei; Zou, Xiao-bing; Zhu, Feng-lei (Frontiers in Psychiatry, 2023)
There are noteworthy sex disparities in the prevalence of autism spectrum disorders (ASD), while findings regarding the sex differences in core symptoms are inconsistent. There are few relevant studies on sex differences in mainland China. This study was dedicated to deeper understanding of the impact of sex differences on the clinical presentation of ASD with fluent language. We retrospectively studied 301 children with ASD (58 females) and utilized raw scores from the ADI-R and ADOS, and IQ to measure symptomatology. Based on the full-scale IQ (FS-IQ), a binary split of average and below average IQ occurs at 80. Across the entire sample, males and females are comparable in the FS-IQ, while males scored higher in the perceptual reasoning index (PRI) (t = 2.80, p = 0.01). The sex ratio (M/F) is higher for H-IQ children (x2 = 6.12, p = 0.01). In the total sample, both ADI-R and ADOS didn’t find any statistically significant sex differences in the diagnosis compliance rates or the raw domain scores. 15.64%–17.24% of children would be under-diagnosed by the simultaneous use of ADIR and ADOS. H-IQ males exhibit a higher rate of ASD diagnostic conformity in the ADOS communication subcategory domain (x2 = 4.02, p < 0.05). Additionally, children's full-scale scores on the ADOS are greater for males, regardless of whether they are in the subgroups of H-IQ (t = 2.12, p = 0.04) or L-IQ (t = 2.15, p = 0.04), and the reciprocal social interaction domain scores are higher for L-IQ males (t = 2.81, p = 0.01). In general, overall cognitive functioning is similar across males and females with ASD, while males have a higher perceptual reasoning ability. Females with ASD are more likely to have comorbid intellectual impairment, which requires more support. There is no discernible sex difference in the core symptoms of ASD among school-aged children and adolescents with fluent language, until a subgroup analysis based on IQ is conducted. Intelligence plays a key role in sex-based differences in the core symptoms of ASD.